Relationship between Personality and Academic Motivation in Education Degrees Students - Ana María de Caso Fuertes; Jana Blanco Fernández; Mª de los Ángeles García Mata; Alfredo Rebaque Gómez; Rocío García Pascual (MDPI AG, 2020)
The present study aims to understand the relationship between the big five factors of personality and academic motivation. In addition, the following variables are taken into consideration; sex, age and type of educational studies. A quantitative methodology is used, in base to a not experimental, correlational study. The sample is composed of 514 students of the Faculty of Education of Leon's University, between the three education degrees. To gather the information, participants were asked to complete the Learning and Motivation Strategies Questionnaire (CEAM) and the Personality Questionnaire Five Factor Inventory (NEO-FFI). The results show the significant relationship between personality facets and motivation variables. It should be noted that female results were higher in the values of intrinsic motivation, motivation towards teamwork, neuroticism, and kindness, and the male results were higher in self-efficacy. Additionally, it was observed that intrinsic motivation decreases progressively from the first to the fourth year of the degree, the need for recognition decreases in the two last study years, and the openness to experiences is higher in the last year of the degree. Finally, Social Education students are those that show a higher intrinsic motivation, self-efficacy, total motivation, openness to experiences, and neuroticism, while Primary Education students' results were higher in the need for recognition.